Philosophy of Education. - Richard, Pring (Continuum International Pub. Group, 2005)
This book for the first time brings together Professor Pring's thoughts on the philosophy of education and is his first global treatment of the subject. His writings reflect a consistency of thought about educational theory and educational aimsand the consequence of both for the nature and practice of educational research. Professor Pring draws together the different themes, providing a distinctively philosophical perspective on educational theory and practice. This perspective challenges many of the ideas, which underpin government policy, impoverish educational practice and weaken education.